Education service marketing management - Amril Nurman; Edi Harapan; Nila Kesumawati (Global Econedu, 2021)
Good management will lead to the realization of the expected marketing, because marketing management is responsible for how the school's efforts to achieve the objectives set in its marketing, such as promoting schools to satisfy consumers and service quality. Marketing management needs to be considered by schools because it will determine the number of students who will enroll in the school. However, in marketing education that must be considered not only outside of school, such as placing advertisements, but also improving the internal school itself. Because with the existence of quality resources, it will give birth to a good image in the eyes of the community. Remember that consumer satisfaction must take precedence in this activity.